Aspek Reproduksi Rajungan (Portunus Pelagicus) Yang Didaratkan Di Pesisir Ujung Pantai Selatan Lombok Timur - Lisnawati Lisnawati; Karnan Karnan; Abdul Syukur (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to describe aspects of the reproductive biology of a blue swimming crab (Portunus pelagicus) that landed at the southern end of the coast of East Lombok during the period November 2023 to April 2024. The study used a descriptive design with a quantitative approach to measure and analyze data through direct observation. Data included carapace width, body weight, gonad maturity stages, and gonad somatic index (GSI) of P.pelagicus. The results showed that the male P.pelagicus population was more dominant than females every month. P.pelagicus body weight varied, with significant increases in certain months caused by spawning. Analysis of the relationship between carapace width and body weight showed positive allometric growth, with b values of 3.17 for males and 3.10 for females, indicating that body weight gain was faster than carapace width. The maturity stages of the P.pelagicus gonads were mostly at stages I and II, with a few reaching stages III and IV. The average gonad maturity stages increased from 2.42% in November to a peak of 5,83 % in February, then decreased in the following months. The primary spawning time occurs from December to February, characterized by changes in gonad color and a decrease in the body weight of the P. pelagicus after spawning. Hopefully, this study’s results can positively contribute to the sustainable management of crabs (P. pelagicus).